Integrating Health and Social Services in Finland: Regional Approaches and Governance Models - Tiirinki Hanna; Sulander Juhani; Sinervo Timo; Halme Saija; Keskimäki Ilmo (Ubiquity Press Ltd., 2022)
Introduction: The study explores regional approaches to integrated care, focusing on regions with regular municipality-based and integrated unified health and social care administration. The aim is to describe a governance approach that supports care integration in the regions. Methods: The study draws on analysis of integrated care governance using an extensive collection of administrative documents (n = 176) on regional health and social services within 20 specialised care authorities. The document data were supplemented with interviews of national health and social system evaluation officers. In our analysis, we used deductive content analysis and identified conceptual approaches of social and health care integration according to elements of integrated care governance. Results: Overall, integrated care governance was relatively well advanced. All regional authorities had established at least some preconditions for integrated governance. The stage of integration varied in the different elements of integrated care governance. The regions with unified integrated administrations enabled the more advanced models of integrated care. Conclusions: Various models for cooperation between regional health and social care authorities have emerged in the regions to identify good integrated care practices. The study suggests that the applied theoretical framework and presented elements of integrated care governance can be used to monitor development of care integration.